Loss of ARID1A Expression in Gastric Cancer: Correlation with Mismatch Repair Deficiency and Clinicopathologic Features - Kim, Kyung-Ju (J Gastric Cancer, 2015)
PURPOSE: The AT-rich interactive domain 1A (ARID1A) gene encodes BRG1-associated factor 250a, a component of the SWItch/Sucrose NonFermentable chromatin remodeling complex, which is considered a tumor suppressor in many tumors. We aimed to investigate the prognostic significance of ARID1A expression in gastric cancers and explore its relationship with clinicopathologic parameters such as mismatch repair protein expression. MATERIALS AND METHODS: Four tissue microarrays were constructed from 191 resected specimens obtained at Soonchunhyang University Cheonan Hospital from 2006 to 2008. Nuclear expression of ARID1A was semiquantitatively assessed and binarized into retained and lost expression. RESULTS: Loss of ARID1A expression was observed in 62 cases (32.5%). This was associated with more frequent vascular invasion (P=0.019) and location in the upper third of the stomach (P=0.001), and trended toward more poorly differentiated subtypes (P=0.054). ARID1A loss was significantly associated with the mismatch repair-deficient phenotype (P=0.003). ARID1A loss showed a statistically significant correlation with loss of MLH1 (P=0.001) but not MSH2 expression (P=1.000). Kaplan-Meier survival analysis showed no statistically significant difference in overall survival; however, patients with retained ARID1A expression tended to have better overall survival than those with loss of ARID1A expression (P=0.053). In both mismatch repair-deficient and mismatch repair-proficient groups, survival analysis showed no differences related to ARID1A expression status. CONCLUSIONS: Our results demonstrated that loss of ARID1A expression is closely associated with the mismatch repair-deficient phenotype, especially in sporadic microsatellite instability-high gastric cancers.